CHANCAY FUNERARY CONTEXTS IN MACATON, CHANCAY-HUARAL - van Dalen Luna, Pieter (2012)
We present the results of investigations carried out in early2009 at the archaeological site of Cerro Macatón, one of the most important sites in the lower valley of the river Chancay-Huaral. This site, consisting of a large funeral with a sector area with residential architecture has been the most extensive area of valley funeral. Excavations allowed us to identify several funerary contexts in which the recurrence was the placement of individuals with in bales, which is an opportunity to know their characteristics.